Linking a rural sanctuary with ancient metallurgy at Kataliondas Kourvellos (Cyprus) - Birchler Emery, Patrizia; Beck, Julien; Agapiou, Athos; Constantin, Dragos; Lysandrou, Vasiliki; Merminod, Bertrand; Themistocleous, Kyriakos (BAF-Online: Proceedings of the Berner Altorientalisches Forum, 2025)
Kataliondas Kourvellos is located at the base of an unusual rock knob, in the lower Troodos foothills, about 20 kilometers south of Nicosia. Recent excavations by the University of Geneva revealed that the site was occupied both in the Pre-Pottery Neolithic period, at the end of the 8th millennium BCE, and in the Cypro-Classical period, in the 4th century BCE.During the Cypro-Classical period, the site seems to have functioned as a rural sanctuary, but the purpose of its location there is not clear: among other explanations, one could be its link with the mining, smelting, and/or trade of metal resources (the lower Troodos foothills have been exploited since the Bronze Age for their copper and other mineralogical resources).